Sosialisasi dan Dampak Budaya Organisasi - André A. Hardjana (Jurnal ILMU KOMUNIKASI, 2010)
Abstract : Interest in corporate culture rapidly grew among organization and management researchers and practitioners in Indonesia since 1990. They were impressed by the concept of strong corporate culture which according to research reports was closely related to high corporate performance. In fact, they were so excited by the fact that strong corporate culture could be a competitive advantage in the era of global competion. This article describes that building a strong corporate culture needs a consistent socialization for values internalization and effective behavioral practice. In addition, socialization is a continuing learning process beyond initiation programs for new employees which involves reward system consistency as well as a powerful idden hierarchy known as the company’s cultural network.